2018
DOI: 10.3390/molecules23123127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Zero Valent Iron Performance in Heterogeneous Fenton and Fenton-Like Processes: A Review

Abstract: Heterogeneous Fenton processes with solid catalysts have gained much attention for water and wastewater treatment in recent years. In the field of solid catalysts, zero valent iron (ZVI) is among the most applicable due to its stability, activity, pollutant degradation properties and environmental friendliness. The main limitation in the use of ZVI in heterogeneous Fenton systems is due to its deactivation in neutral and alkaline conditions, and Fenton-like processes have been developed to overcome this diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 110 publications
2
49
0
2
Order By: Relevance
“…However, generation of large values of iron-containing sludge and limited operating pH range (an optimal run is performed at pH ~3) of EF process urges the development of EF-like process which can be operated in a completely heterogeneous and neutral system. 55,56 60 . In this case, we thus evaluated the Fenton-like performance of NiOC catalyst in neutral system and observed that NiOC catalyst exhibited a more effective degradability compared with that of O-C catalyst under the same experiment conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, generation of large values of iron-containing sludge and limited operating pH range (an optimal run is performed at pH ~3) of EF process urges the development of EF-like process which can be operated in a completely heterogeneous and neutral system. 55,56 60 . In this case, we thus evaluated the Fenton-like performance of NiOC catalyst in neutral system and observed that NiOC catalyst exhibited a more effective degradability compared with that of O-C catalyst under the same experiment conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidizing power of the Fenton system degradation mechanism is based on creation • OH radicals by decomposition of H2O2 onto iron ion (Fe 2+ ) promoter. 37 It was demonstrated previously that pH affects the iron ion oxidation, and subsequently it affects the rate of hydroxyl radicals generation. 38 The optimal range of pH has been reported to be 2 -4.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, direct use of ferrous salt catalyst results in rapid and useless consumption of Fe 2+ as well as overload of ferric ions in the treatment medium [ 12 , 13 ]. Therefore, several studies have reported the use of zero valent iron (ZVI) as the heterogeneous source of Fe 2+ ions in the Fenton process [ 14 , 15 ]. In this technology, ZVI metal in contact with aqueous solution corrodes spontaneously producing ferrous ions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%